Relation Of Education, Age, And Parity To The Choice Of Family Planning Methods - Maryuni Maryuni (Alma Ata University Press, 2019)
Indonesia is the fourth largest contributor to the population in the world after China, India and the United States. The 2017 IHDS showed the total fertility rate (TFR) was 2.4 children per woman. One program to reduce population growth rates and TFR is through the Family Planning (KB) program. This study aims to determine the relationship of education, age and parity to the choice of contraceptive methods for long and short-terms in Tanjung Anom Village, Salaman Subdistrict, Magelang Regency, Central Java Province. This research is descriptive analytic with cross sectional method. The data collection was done in October 2015. The study sample was women of childbearing age who used contraception in both long and short terms, as many as 46 people. The research instrument used was a questionnaire. Data was analyzed by univariate and bivariate. The result of the study showed that there was no significant relationship among education, age and parity towards the choice of both long and non-long contraception methods. The selection of contraceptive method is not only influenced by education, age and parity, but also by Socio-Demographic factors, Socio-Psychological factors, and health services